Projection 0f Labor Needs and Productivity to Reduce Unemployment - Agusalim, Lestari (JEJAK: Jurnal Ekonomi dan Kebijakan, 2016)
The purpose of this study is to estimate the amount of labor needs and productivity in Banten Province from 2016 until 2020. By estimating the needs and productivity of the labor, the government can use this information to create the appropriate policies in order to reduce the open unemployment rate (OUR) in Banten Province. According to BPS data in 2014, OUR of Banten Province was the highest among other provinces in Java and second highest in Indonesia after Maluku. This study used the quantitative method, which are the exponential and geometric methods to project the labor needs. Other than that, this study used the descriptive method to interpret the quantitative data. The result showed that (1) from 2016 until 2020 there will be an increasing condition of employment, (2) from 2010 until 2014, the highest labor productivity were from electricity, gas and water sector. However from 2016 – 2020, the highest labor productivity will be from financing, insurance, real estate, land, and business services. (3) The number of OUR is expected to decrease annually. Meanwhile OUR in 2016 which is 7.39 percent will decrease to 3.94 percent in 2020.